A fully integrated 2.4dB NF capacitive cross coupling CG-LNA for LTE band - Abdelhamid, Amr A.; Özgün, Mehmet Tamer; Doğan, Hakan (Springer, 2019)
This paper presents a common gate low noise amplifier utilizing a passive feedback network that provides a competitive and highly integrated front-end solution for mobile handset devices. This design utilizes a resistive load instead of the inductive one used in other designs to reduce the on-chip silicon area. The design does not need an external matching network which decrease the area of the PCB while achieving a sufficient input impedance matching, S-11. It achieves a measured gain higher than 20dB, noise figure less than 3dB and input referred third order intercept point (IIP3) value higher than-2.5 dBm at 2.3GHz. The design is implemented in 65nm UMC CMOS technology, occupies a total area of 0.065mm(2) and consumes 5mW from a 1.4V supply.
WOS: 000460681500015
Keywords: LNA; Capacitive Cross-Coupling; Common Gate; RF Receivers